Antecedents and Consequences of Student-Athletes’ Contentment With Academic Services - Hazzaa, Rammi N.; Sonkeng, Katja; Yoh, Taeho (Journal of Intercollegiate Sport, 2018)
The purpose of this study sought to investigate factors that influence student-athletes’ satisfaction with academic services within athletics departments. Additionally, we examined the relationship between student-athletes’ satisfaction and academic performance (i.e., GPA). A total of 226 NCAA Division I student-athletes from a Midwestern university competing in a mid-major conference participated. A survey consisting of 22 questions was created to assess the satisfaction of the four major factors (facilities, staff, tutoring, and advising programs) of academic advising services. Results revealed that student-athletes were satisfied with academic services, but satisfaction differed among class levels, with freshman athletes reporting lower levels of satisfaction than junior and senior athletes. Additional results showed that facilities and staff have significant influences on student-athletes’ satisfaction with academic services. Furthermore, there was a significant relationship between student-athletes’ satisfaction and GPA. The findings provide partial support for the proposed theoretical model, which suggests that athletics departments should provide adequate, accessible academic facilities and hire properly-trained staff.